Misuser Inventions and the Invention of the Misuser: Hackers, Crackers and Filesharers. - Söderberg, Johan (Science as Culture, 2010)
The conflicts which have erupted over hacking, cracking and filesharing offer a stepping-stone for rethinking the involvement of users in innovation processes. As technical design processes invariably proceed in the shadow of established relations of social power, we can expect them to encompass conflicts over what constitutes the creative use of technology versus its misuse. The figure of the misuser calls attention to the importance of antagonistic relations in the mutual shaping of technology and society. Constructivist STS research has been criticised for neglecting the importance of antagonistic relations in favour of an emphasis on the limitless mutability of human/machine hybrids. The transformative effects of innovation processes on interests and subjectivities cannot be denied. But the induction of such transformations might be interpreted as a method through which struggles are conducted. This dynamic is particularly forthcoming in the case of filesharing, where users innovate precisely in order to overthrow the material practices upon which intellectual property law is founded. It is the intervention of law enforcement agencies in the process of drawing the line between users and misusers that makes the presence of an antagonistic relation manifest.